Social entrepreneurship: The development of strategic process and leadership - Munaf, Muhamad Irham (2016)
The primary objective of social entrepreneurship is to create social value. The effective social value creation process has to be strategically planned and analysed. However, the need of the process seems essential to assure the social mission is achieved and the organisation continuously improves the performance Nevertheless, some scholars argue that social entrepreneurs have less strategic management and organisational skills, which may complicate to attain the purpose effectively and efficiently. This paper will review the existing literature and build a model of the strategic process in social entrepreneurship based on the combination of the research. Two case studies will be provided to analyse and evaluate the leadership style of social entrepreneurs in order to discover the ideal leadership to manage the strategic process in a social enterprise. The findings suggest that the strategic process might be applied in social entrepreneurship process in order to certain the effectiveness of social value creation. Furthermore, strategic leadership might be an ideal approach for social entrepreneurs to lead the social enterprise on pursuing social value and sustaining the organisation in the long term.